Reconstructive plastic surgery for congenital adrenal hyperplasia in girl - Daulet Zharassov (National Scientific Medical Center, 2016)
Congenital adrenal hyperplasia - congenital disease the cause of which is a genetic defect in the enzymes involved in the synthesis of corticosteroids, and transport proteins leading to hyperandrogenism and is accompanied by abnormalities of internal and external genitalia of girls (virilization). It occurs with a frequency according to the different sources from 1: 5000 to 1: 67000. The article is devoted to the clinical case of reconstructive surgery on the genitals of the girl with impaired formation of sex, namely with congenital adrenal hyperplasia.